Searching for antimalarial agent from Indonesian Combretum indicum and Magnolia figo - Nugraha, Ari Satia; Pratoko, Dwi Koko; Triatmoko, Bawon; Pratama, Antonius Nugraha Widhi; Rohmatillah, Wilda Nur; Laksono, Tinton Agung (Proceedings of the International Conference on Green Technology, 2019)
The archipelagic country of Indonesia has been an endemic area of malaria in which the Indigenous people of Indonesia have used medicinal plants to fight against plasmodial parasites. The study focused on two medicinal plants of Indonesia, namely Combretum indicum and Magnolia figo. Phytochemical, spectroscopic, and bioactivity assay protocols were performed. The experiments resulted in the major components detected were terpenoids and phenolic constituents. The bioassay indicated significant antimalarial potency of the crude methanol extract of leaves of Combretum indicum and Magnolia figo.